1990
DOI: 10.1164/ajrccm/142.6_pt_1.1272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet-activating Factor Receptor Antagonism on Endotoxin-induced Lung Dysfunction in Awake Sheep

Abstract: To test the hypothesis that PAF partially mediates endotoxin-induced lung dysfunction, we studied the effects of two structurally dissimilar PAF receptor antagonists (SRI 63-441 and WEB 2086) on endotoxin-induced lung dysfunction in chronically instrumented awake sheep. Each animal was studied three times in varied order: infusion of endotoxin alone (Escherichia coli endotoxin 0.5 micrograms/kg over 20 min [E]), infusion of the competitive platelet-activating factor (PAF) receptor antagonist alone, or with end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 15 publications
3
29
0
Order By: Relevance
“…An exaggerated vasoconstrictor response of PAs in ARDS/ ALI is important as it may contribute to increased pulmonary vascular resistance, pulmonary hypertension, and lung edema (4,6). Other authors have found increased sensitivity to HPV in perfused lungs from endotoxin-treated rats (12,18), in isolated PA exposed in vitro to endotoxin (16), or in the isolated blood-perfused rat lung after treatment with TNF-α (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An exaggerated vasoconstrictor response of PAs in ARDS/ ALI is important as it may contribute to increased pulmonary vascular resistance, pulmonary hypertension, and lung edema (4,6). Other authors have found increased sensitivity to HPV in perfused lungs from endotoxin-treated rats (12,18), in isolated PA exposed in vitro to endotoxin (16), or in the isolated blood-perfused rat lung after treatment with TNF-α (15).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary vascular dysfunction is a known feature of ARDS/ALI. Pulmonary vascular resistance and pulmonary arterial pressure are elevated in patients with ARDS (4) and in animal models of ALI induced by sepsis/endotoxin (5,6) or HVt ventilation (7). Another key feature of ARDS/ ALI is the mismatch of ventilation and perfusion leading to Pulmonary Vascular Dysfunction Induced by High Tidal Volume Mechanical Ventilation* intrapulmonary shunting due to an impaired hypoxic pulmonary vasoconstriction (HPV) (8), which contributes to the systemic hypoxemia in ARDS/ALI (9,10).…”
mentioning
confidence: 99%
“…Furthermore, endotoxin infusion causes an increase in the levels of PAF [29]. Pretreatment with PAF antagonists inhibits both the rise in TXA 2 and the pulmonary pressor response to endotoxin [30].…”
Section: Discussionmentioning
confidence: 99%
“…10 Briefly, 2 ng of tetradeuterated thromboxane B 2 was introduced into 100 L of each sample as an internal standard. Samples were acidified with 0.5% formic acid and extracted with ethyl acetate.…”
Section: Analytical and Statistical Methodsmentioning
confidence: 99%